200k views
5 votes
1/2r + 2 (3/4r - 1) = 1/4r + 6



2 Answers

7 votes

Let's solve your equation step-by-step.

Step 1: Simplify both sides of the equation.

1/2r + 2 (3/4r - 1) = 1/4r + 6

Step 1: Simplify both sides of the equation.

1/2r + 2 (3/4r - 1) = 1/4r + 6

1/2r+(2)(3/4r)+(2)(-1)=1/4r+6(Distribute)

1/2r+3/2r+-2=1/4r+6

(1/2r+3/2r)+(-2)=1/4r+6(Combine Like Terms)

2r+-2=1/4r+6

2r-2=1/4r+6

Step 2: Subtract 1/4r from both sides.

2r-2-1/4r=14r+6-14r

7/4r-2=6

Step 3: Add 2 to both sides.

7/4r-2+2=6+2

7/4r=8

Step 4: Multiply both sides by 4/7.

(4/7)*(7/4r)=(4/7)*(8)

r=32/7

Answer: r=32/7

hope this helps :)

User Thomas L Holaday
by
5.7k points
1 vote

Answer:

r=32/7

Explanation:

User Mircea Dragota
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.